Extreme learning machine for user location prediction in mobile environment - Mantoro, Teddy; Olowolayemo, Akeem; Olatunji, Sunday O.; Ayu, Media Anugerah; Md. Tap, Abu Osman (Emerald Group Publishing Limited, 2011)
Purpose – Prediction accuracies are usually affected by the techniques and devices used as well as the algorithms applied. This work aims to attempt to further devise a better positioning accuracy based on location fingerprinting taking advantage of two important mobile fingerprints, namely signal strength (SS) and signal quality (SQ) and subsequently building a model based on extreme learning machine (ELM), a new learning algorithm for single-hidden-layer neural networks.